A secure method against frequency attack for pattern query on encrypted string data - Ravan, Rama Roshan; Norbik Bashah Idris; Faculty of Advanced Informatics School (2013)
Thesis (Sarjana Sains (Keselamatan Maklumat)) - Universiti Teknologi Malaysia, 2013